PENGARUH BIAYA BAHAN BAKU, BIAYA TENAGA KERJA LANGSUNG, DAN BIAYA OVERHEAD PABRIK TERHADAP HARGA JUAL PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI - Ade Pipit Fatmawati; Afra Al Mumtahanah (Universitas Logistik dan Bisnis Internasional, 2022)
Consumer Goods Industry Sector Companies are manufacturing companies that produce people's daily needs. There is a phenomenon about the increase in selling prices so that it attracts the interest of the author to research more deeply about it. This study aims to determine the effect of raw material costs, direct labor costs, and factory overhead costs on the selling price of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange for the 2020 period, either individually or simultaneously. This research is quantitative research. The hypothesis is determined using a two-tailed test (two-tailed). The analytical technique used is normality test, product moment correlation, multiple correlation analysis, multiple linear regression analysis, coefficient of determination analysis, t test and F test. Statistical calculations using SPSS for windows version 26. This study shows that the cost of raw materials, direct labor costs, and factory overhead costs have a significant effect on the selling price, either partially or simultaneously.”